Attracting foreign direct investments into Burundi (Africa) : lessons from Singapore. - Evariste, Nduwayo. (2008)
The objective of this study is to explore what lessons can other developing countries, Burundi in particular can learn from this success story. On one hand, what the reasons are behind this economic stagnation of countries like Burundi, and on the other hand, what the drivers of economies like Singapore have been.